EFFECT OF THE PLASTIC COVER COLOR AND ELECTROCUTION IN SOME VEGETATIVE GROWTH INDICATORS AND PARTHENOLIDE CONTENT IN LEAVES OF TANACETUIM PARTHENUIM L PLANT. - Z. J. Al-Mousawi; S.O.Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This research was carried out in the scientific experiments field of the colleg of Agriculture - University of Baghdad, during the agricultural season 2015-2016 to study the effect of the plastic cover color and electric shocks in the vegetative growth indicators and Parthenolide content in the leaves, the expirements conducted according to the randomized complete block design (RCBD) (Split plot design) the first factors (Main plot) was the plastic cover color (transparent, yellow, red and blue) and the second factor (Sub plot) incorporates four levels of electrocution (0,2,4,6 Amp) for 4 minutes, thereby resulting 48 experimental units (4 × 4 × 3) as the experimental unit contains 10 plants.The differences amonge means were tested using LSD test at a level of probability of 0.05. The results showed superiority of the treatment of the caver blue (B) an increase of plant height and leaf area and chlorophyll A and B total chlorophyll, reaching 18.50 cm , 28.73 , 1.581 , 1.136, and 3.460 mg 0.100 g-1 fresh weight respectively), and the superiority of the transaction yellow cover ((Y to increase the number of leaves and fresh and dry vegetative growth (141.50 , leaf .plant -1 , 65.27 g.plant-1 and 22.02 g.plant-1), respectively, and outperformed the treatment of red cover (R) outperforming increase the number of branches, which reached 12.67 branch.plant-1, and the treatment of electrocution level (4 Amp) has outperformed significantly in charactesistics vegetative growth, which included (plant height, number of leaves, leaf area, leaf content of total chlorophyll and chlorophyll A, B, fresh and dry weight of shoot and the content of the leaves from the Parthenolide (18.41 cm and 149.70 leaf.plant-1and dcm2.pant-1and 26.29 g.plant-180 0.85 g.plant-1 and 30.067 g and 25.70 µg.g-1) respectively, the treatment of the overlap between the color of the cover electric stun significant effect on vegetative growth indicators have superior treatment (BA2) a significant increase in plant height and leaf area and the content of the leaves of chlorophyll A,B total (20.33 cm and 35.65cm2.plant-1and 1.993 and 1.230 and 3.969 mg.100g-1fresh weight respectively, and the superiority of the treatment of overlap (RA3) in the number of branches vegetative (17.33 branch.plant-1) and the treatment of overlap (YA2) in the number of leaves, fresh and dry weight of branches (167.67 leaf.plant-1and 95.82 g and 37 0.98 g), respectively.It can be conclude that of the the color plastic cover and electric shocks had significant effect on vegetation and stimulate the growth and prodation of parthenolide in leaves.